Dampak Penyakit KEK Pada Ibu Hamil - Alyssa Atikah Putri; Shella Salsabila (Student Scientific Creativity Journal, 2023)
Chronic energy shortage in pregnant women can have a number of consequences significant negative impacts on the health and development of the mother and the fetus. The study aims to analyze the impact of chronic energy deficiency on pregnant women based on an overview of the existing literature. The study involved analysis and synthesis of a variety of reliable sources that included scientific research and related health reports. Results of literature reviews suggest that chronic energy deficiency in pregnant women can lead to a variety of health problems. Pregnant women who experience chronic energy shortages have a higher risk of experiencing persistent fatigue, unwanted weight loss, and a decrease in physical strength. In addition, chronic energy shortages can also cause problems on the mother’s immune system, increase the risk of infection, and affect the body’s ability to recover after childbirth. To raise awareness about the dangers of chronic energy shortages on pregnant women, further research is needed to understand the underlying mechanisms and the effectiveness of appropriate interventions. Thus, this information can be used to improve prenatal care and provide the necessary support for pregnant women to ensure optimal health and development for the mother and fetus.